2018
DOI: 10.3390/min8110483
|View full text |Cite
|
Sign up to set email alerts
|

An Improved High-Pressure Roll Crusher Model for Tungsten and Tantalum Ores

Abstract: An improved approach is presented to model the product particle size distribution resulting from grinding in high-pressure roll crusher with the aim to be used in standard high-pressure grinding rolls (HPGR). This approach uses different breakage distribution function parameter values for a single particle compression condition and a bed compression condition. Two materials were used for the experiments; altered Ta-bearing granite and a calc-silicate tungsten ore. A set of experiments was performed with consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…These results are in line with an observation from our SEM-EDS investigation of unconcentrated samples, despite the much more limited number of ore-bearing particles studied. A simple conceptual model for the induced fractionation of minerals during crushing is presented in Figure 12, which is based on the presented results and previous studies [25,31,32]. Fractures and microfractures in matrix minerals possibly control the overall breakage behavior of the rock; as a consequence of this, most of the finer particles are generated from breakage of matrix minerals.…”
Section: Penouta Materials Characteristicsmentioning
confidence: 71%
See 1 more Smart Citation
“…These results are in line with an observation from our SEM-EDS investigation of unconcentrated samples, despite the much more limited number of ore-bearing particles studied. A simple conceptual model for the induced fractionation of minerals during crushing is presented in Figure 12, which is based on the presented results and previous studies [25,31,32]. Fractures and microfractures in matrix minerals possibly control the overall breakage behavior of the rock; as a consequence of this, most of the finer particles are generated from breakage of matrix minerals.…”
Section: Penouta Materials Characteristicsmentioning
confidence: 71%
“…The case study was performed on two~1 ton samples from the Penouta open pit mine, collected by university of Centres Cientifics i Tecnològics de la Universitat de Barcelona during January 2015, as a part of a multi-partner research collaboration (OPTIMORE, project number 642201) [25,[28][29][30][31][32]. Due to potential mineralogical variations, samples of the mineralized leucogranite were collected from different parts of the open pit.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, there is no single opinion as to simulating this very characteristic [5] considers simulation of curves of granulometric composition of crush products and notes that crushing results can be controlled by selecting a particular value of pressure on the ore bed. [6] applies the distribution function of disintegration of ore lumps that is associated with the characteristic of the initial material to assessing ore sizes [7] also indicates that besides the ore disintegration distribution, the clearance between rollers has a great impact on the size of crush products. The authors of [8] note that the granulometric composition of products is influenced by the location of rollers.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Gravity separation studies focussed in a particular sector of the Penouta tailings have been reported [35], as well as studies on metallurgical treatments [36]. These studies, along with the previous studies on crushing [37] and milling [32,38], provide a broad understanding of the Penouta ore processing. However, in this study, the mineralogical characteristics of ore materials, tailings, and leucogranite outcropping are characterized.…”
Section: Introductionmentioning
confidence: 99%